Introduction to leadership : concepts and practice / Peter G. Northouse. - Northouse, Peter G. (Sage, 2025)
This title provides readers with a clear, concise overview of the complexities of practicing leadership and concrete strategies for becoming better leaders. The text is organized around key leader responsibilities such as creating a vision, engaging strengths, and managing conflict. Case studies, self-assessment questionnaires, observational exercises, and reflection and action worksheets engage readers to apply leadership concepts to their own lives.